Detection of Insomnia and Its Relationship with Cognitive Impairment, Depression, and Quality of Life in Older Community-Dwelling Mexicans - Elsa Correa-Muñoz; Raquel Retana-Ugalde; Víctor Manuel Mendoza-Núñez (Diagnostics, 2023)
Sleep disturbances are one of the most frequent health problems in old age, among which insomnia stands out. It is characterized by difficulty falling asleep, staying asleep, frequent awakenings, or waking up too early and not having restful sleep, which may be a risk factor for cognitive impairment and depression, affecting functionality and quality of life. Insomnia is a very complex multifactorial problem that requires a multi- and interdisciplinary approach. However, it is frequently not diagnosed in older community-dwelling people, increasing the risk of psychological, cognitive, and quality of life alterations. The aim was to detect insomnia and its relationship with cognitive impairment, depression, and quality of life in older community-dwelling Mexicans. An analytical cross-sectional study was carried out in 107 older adults from Mexico City. The following screening instruments were applied: Athens Insomnia Scale, Mini-Mental State Examination, Geriatric Depression Scale, WHO Quality of Life Questionnaire WHOQoL-Bref, Pittsburgh Sleep Quality Inventory. The frequency of insomnia detected was 57% and its relationship with cognitive impairment, depression, and low quality of life was 31% (OR = 2.5, 95% CI, 1.1–6.6. p < 0.05), 41% (OR = 7.3, 95% CI, 2.3–22.9, p < 0.001), and 59% (OR = 2.5, 95% CI, 1.1–5.4, p < 0.05), respectively. Our findings suggest that insomnia is a frequent clinical disorder that is not diagnosed and a significant risk factor for cognitive decline, depression, and poor quality of life.